Acute Antinflammatory Effect of Marsdenia tinctoria Leaf Water Extract in Carragenan-induced Rats - Supito, Sarasvati Sekar Ayu; Sutjiatmo, Afifah Bambang; Kusumawardhana, Gelar Taufiq; Vikasari, Suci Nar (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2025)
Introduction: Tarum areuy (Marsdenia tinctoria) is a plant whose efficacy has not been widely explored. Traditionally used for infections and inflammation related disease.. Aims: To determine the anti-inflammatory effect of M. tinctoria leaf water extract on animals induced by carrageenan.Methods: Extract preparation by boiling in water. Animals were divided into groups, namely control, comparison (diclofenac sodium 4.5 mg/kgBW) and M. tinctoria leaf water extract (20, 40, 80 mg/kgBW). Induction of 0.1 mL of 1% carrageenan was given as much as intraplantar and the test preparation was given orally. Inflammatory and inflammatory inhibition percentages were measured every 30 minutes for 240 minutes. The t-test was utilized in data analysis.  Result: All test doses of M. tinctoria leaf water extract was effective to reduce inflammation in comparison to the control (p<0.05). A dose of 20 mg/kgBW was the optimal anti-inflammatory.. Conclusion: M. tinctoria leaf water extract has the potential as an anti-inflammatory.